EFEKTIVITAS KOMUNIKASI INTEREPERSONAL PENGGUNA MASKER SAAT TRANSAKSI JUAL-BELI DI PASAR PEJUANG BEKASI - Dessy Andamisari; Wulan Furrie (Interpretasi: Communication & Public Relations, 2021)
The use of masks during the Covid-19 pandemic is an obligation for everyone without exception. The use of masks is a way that is considered quite effective in preventing droplets / splashes or droplets of the Covid-19 virus from being exposed to other people. However, the use of masks can be one of the obstacles / obstacles to creating interpersonal communication, especially when buying and selling transactions between buyers and traders in traditional markets.This research is carried out by careful and detailed observation of a phenomenon, highlighting current problems with the data collection process that allows researchers to describe the situation more completely. The results showed that the use of masks is a dilemma for both buyers and traders when making buying and selling transactions. On the one hand, the use of masks is an obligation that must be adhered to according to the health protocol policies established by the government, but on the other hand, it can affect the effectiveness of interpersonal communication between the two parties. Solutions that can be done by both parties include making eye contact, understanding body language and playing volume, tone and pauses, so that interpersonal communication can continue to be effective.